Say it isn't so : art trains its sights on the natural sciences = Naturwissenschaften im Visier der Kunst. - Weserburg Museum für moderne Kunst, Bremen (Heidelberg : Kerber Verlag Heidelberg, 2007)
Collier, Brian ; Dion, Mark ; Hakansson, Henrik ; Hesse, Frank ; Höller, Carsten ; Keller, Christoph ; KissPal, Szabolcs ; Lang, Gerhard ; M+M ; Nicolai, Carsten ; Nicolai, Olaf ; Petzet, Nana ; Pollmann, Tyyne Claudia ; Radtke, Theda ; Rickli, Hannes ; Sachs, Hinrich ; Shawcross, Conrad ; Stöger, Günter ; Turk, Herwig ; Walgenbach, Judith
biog. + tentoongestelde werken p. 248-253
This catalogue is being published on the occasion of the exhibition "Say it isn't so - Naturwissenschaften im Visier der Kunst/Art trains its sights on the natural sciences" in Wederburg, Museum für moderne Kunst, Bremen, 12.05.2007 - 16.09.2007
Duits en Engels
boek